Fusarium Keratitis Treatment and Management: A Case Series of Emerging Organism - Patil, Rajashri; Mukhida, Sahjid; Ajagunde, Jyoti; Vyawahare, Chanda; Gandham, Nageswari; Algule, Shital Algule (AL-Kindy College Medical Journal, 2024)
Infectious keratitis may be caused by viruses, bacteria, parasites, and fungi. Noninfectious can be caused by injury to the cornea, dryness of the cornea, allergies, and improper use of contact lenses. Fungi commonly responsible for corneal ulcers are Aspergillus (most common), Candida, and Fusarium. Both Aspergillus and Fusarium account for about one-third of all traumatic infectious keratitis. In the current case series, we submit 4 cases of Fusarium keratitis. A microbiological investigation like KOH mount is an important test that can confirm the presence of the fungal infection in samples. Topical and systemic anti-fungal treatment combinations give better outcomes in fungal keratitis patients. Culture is the gold standard, and fusarium species are rapid growers. All suspected patients should be screened for fungal culture in their primary visit to prevent further complications and disability.